A theory for bistable vibration isolators. (15th March 2022) - Yan, Bo; Yu, Ning; Ma, Hongye; Wu, Chuanyu
Highlights: A general theory for bistable vibration isolators (BVIs) is established. Force and displacement transmissibilities are derived to evaluate the bistable vibration isolation performance. A BVI can produce negative and softening stiffness to broaden the isolation band. A shallower potential barrier is beneficial to the vibration isolation. The transmissibility of BVI can be smaller than 1 in the resonance region during the snap-through. Abstract: Bistable structures have been widely used for vibrational energy harvesting, the corresponding potential vibration isolation application has also received attention recently. This paper presents a general theory for bistable vibration isolators (BVIs) and reveals the bistable vibration isolation mechanism. The nonlinear restoring force and potential energy are obtained through analyzing the general model of BVIs with "three-spring" quasi-zero stiffness (QZS) model. The generalized force and displacement transmissibilities of BVIs are deduced. The theoretical and numerical transmissibilities are calculated. A feasible model of BVIs is applied to quantitatively verify the advantages of BVIs in vibration isolation. The results demonstrate that BVIs can provide negative and softening stiffness characteristics to broaden the isolation band, and a shallower potential barrier and intrawell oscillation are beneficial to vibration isolation. BVIs should be carefully designed to avoid the interwall oscillation to ensure a considerable vibration isolation performance due to the effects of initial equilibrium position. This paper provides a guideline for the design, analysis, and optimization of BVIs.